Measuring the Level of Agreement on the Development of Sustainable Framework for TVET Teacher Education Program in Malaysia - Hamdan, Nor Hidayah; Md Yunos, Jailani; Lai, Chee Sern; Ibrahim, Badaruddin; Munastiwi, Erni (Journal of Technical Education and Training, 2021)
TVET Teacher Education program in Malaysia has been established with the purpose to produce TVET teachers who capable of meeting the criteria of the 21st Century. This study is the first to investigate the agreement level of lecturers in TVET teacher education program on the development of the related sustainable framework. We developed a questionnaire to assess the level of agreement on the domain and elements needed for the sustainable framework for TVET Teacher Education program in Malaysia. We then conducted a survey involving 117 TVET Teacher Education programs lecturers in all Malaysia public universities. The data were analysed using Descriptive Analysis involving the mean score and standard deviation. The result indicates the lecturers perceived the Role of Government [M=6.11; SD = .697] as the highest domain important to the development of the sustainable framework and the Criteria of Sustainable Management System [M=5.72; SD= .843] as the lowest agreed on the importance of the domain. Moreover, the entire sustainable framework perceived a high level of agreement from the respondent. It is believed that with this sustainable framework of TVET Teacher Education program, the criteria of Malaysian TVET teacher produced can be tailored to the need of future education. We recommended that the replication of this study from different field of teacher education program in Malaysia ensure all teachers in Malaysia are qualified and versatile with future education.